2009
DOI: 10.1179/174313208x346918
|View full text |Cite
|
Sign up to set email alerts
|

Neurological deficits associated with the elastase-induced aneurysm model in rabbits

Abstract: Objective: Although the rabbit elastase-induced aneurysm model is currently used widely for endovascular research and device testing, procedural causes leading to animal morbidity and mortality have not yet been clearly described. We conducted a retrospective study to analyse factors contributing to neurological deficits in rabbits that underwent the elastase-induced aneurysm creation procedure at our research center from 2002 to 2005 in order to improve the technique and reduce procedure-related morbidity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…20 Conversely, the short endovascular procedure time of <25 min was shown to minimize complications in the rabbits. 12,14,21 Our experimental group with a relatively short procedure time of 23 ± 2 min suggests a safe model without neurologic deficits. The body weight changes of an experimental animal have been known well to be an important indicator of experimental success.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…20 Conversely, the short endovascular procedure time of <25 min was shown to minimize complications in the rabbits. 12,14,21 Our experimental group with a relatively short procedure time of 23 ± 2 min suggests a safe model without neurologic deficits. The body weight changes of an experimental animal have been known well to be an important indicator of experimental success.…”
Section: Discussionmentioning
confidence: 90%
“…To minimize air embolism or prevent elastase leakage, Liliana et al suggested that the intervention protocol used in this clinical trial could be applied to animal experiments. 12 However, the presented method was a design that was not applied to an actual experiment, and the materials used were several and complicated, which may cause inconvenience to the operator. The procedure of the control group was relatively simpler; however, a phenomenon that elastase was leaked through the robber hub with the hemostatic valve part of the sheath was indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We constructed elastase-induced aneurysms in rabbits [5,6] and implanted three different ESVRs. The devices selected were two that scored the best (devices C and E, Figure 3) and device B that had the same porosity but different pore density than device E. Twenty one (n=9), 90 (n=9) & 180 days (n=12) post-implantation, the aneurysms were evaluated by angiography, the animals were sacrificed, and the vasculatures containing the implants were harvested for histological evaluation.…”
Section: Changes In Flow Physics Due To An Esvrmentioning
confidence: 99%